THE ROLE OF MARKERS GALECTIN-3 AND H-FABR IN CURRENT FORECAST CHRONIC HEART FAILURE IN PATIENTS UNDERGOING STENTING AND CORONARY ARTERY BYPASS GRAFTING, WITH AND WITHOUT TYPE 2 DIABETES - Khaidarova F. A.; Inogamova D. T. (Journals Park Publishing, 2025)
Cardiovascular diseases remain the main cause of death and disability in patients with type 2 diabetes mellitus (DM2) DM2 aggravates the underlying mechanisms of atherosclerosis and heart failure.